Missing Women: Recovering and Replacing Female Activists in Australian Labour History - Brigden, Cathy (Atlantis, 2007)
There is relatively little research about women in labour councils and labour federations. Focusing on the historical and contemporary uses and impact of separate organising, this paper explores key developments in shaping patterns of women's activism through the experiences of women unionists in an Australian labour federation.